The Estimating of the Conditional Density with Application to the Mode Function in Scalar-On-Function Regression Structure: Local Linear Approach with Missing at Random - Bouabsa, Wahiba (Szacowanie gęstości warunkowej z wykorzystaniem modelu w strukturze regresji skalarnej na funkcji: lokalne podejście liniowe z losowym brakiem, 2023)
The aim of this research was to study a nonparametric estimator of the density and mode function of a scalar response variable given a functional variable, when the observations are i.i.d. This proposed estimator is given by combining Missing At Random (MAR) with the local linear approach. Finally, a comparison study based on simulated data is also provided to illustrate the finite sample performances and the usefulness of the local linear approach with MAR to the presence of even a small proportion of outliers in the data.
Econometrics = Ekonometria, 2023, Vol. 27, No. 1, s. 17-32
Keywords: functional data; local linear estimation; conditional mode function; functional non-parametric Statistics; dane funkcjonalne; lokalna estymacja liniowa; funkcja trybu warunkowego; funkcjonalna statystyka nieparametryczna